Protocatechuic Acid Protects Platelets from Apoptosis via Inhibiting Oxidative Stress-Mediated PI3K/Akt/GSK3β Signaling - Ya, Fuli; Li, Kongyao; Chen, Hong; Tian, Zezhong; Fan, Die; Shi, Yilin; Song, Fenglin; Xu, Xiping; Ling, Wenhua; Adili, Reheman; Yang, Yan (Thrombosis and Haemostasis, 2021)
Oxidative stress plays crucial roles in initiating platelet apoptosis that facilitates the progression of cardiovascular diseases (CVDs). Protocatechuic acid (PCA), a major metabolite of anthocyanin cyanidin-3-O-β-glucoside (Cy-3-g), exerts cardioprotective effects. However, underlying mechanisms responsible for such effects remain unclear. Here, we investigate the effect of PCA on platelet apoptosis and the underlying mechanisms in vitro. Isolated human platelets were treated with hydrogen peroxide (H2O2) to induce apoptosis with or without pretreatment with PCA. We found that PCA dose-dependently inhibited H2O2-induced platelet apoptosis by decreasing the dissipation of mitochondrial membrane potential, activation of caspase-9 and caspase-3, and decreasing phosphatidylserine exposure. Additionally, the distributions of Bax, Bcl-xL, and cytochrome c mediated by H2O2 in the mitochondria and the cytosol were also modulated by PCA treatment. Moreover, the inhibitory effects of PCA on platelet caspase-3 cleavage and phosphatidylserine exposure were mainly mediated by downregulating PI3K/Akt/GSK3β signaling. Furthermore, PCA dose-dependently decreased reactive oxygen species (ROS) generation and the intracellular Ca2+ concentration in platelets in response to H2O2. N-Acetyl cysteine (NAC), a ROS scavenger, markedly abolished H2O2-stimulated PI3K/Akt/GSK3β signaling, caspase-3 activation, and phosphatidylserine exposure. The combination of NAC and PCA did not show significant additive inhibitory effects on PI3K/Akt/GSK3β signaling and platelet apoptosis. Thus, our results suggest that PCA protects platelets from oxidative stress-induced apoptosis through downregulating ROS-mediated PI3K/Akt/GSK3β signaling, which may be responsible for cardioprotective roles of PCA in CVDs.
Keywords: anthocyanin; protocatechuic acid; platelet apoptosis; reactive oxygen species; oxidative stress